An in situ DRIFTS mechanistic study of CeO2-catalyzed acetylene semihydrogenation reaction. Issue 14 (27th March 2018) - Cao, Tian; You, Rui; Zhang, Xuanyu; Chen, Shilong; Li, Dan; Zhang, Zhenhua; Huang, Weixin
Abstract : The mechanism of CeO2 -catalyzed C2 H2 semihydrogenation reaction is elucidated with identified surface species. Abstract : CeO2 -Catalyzed C2 H2 semihydrogenation reaction is a newly emerging catalytic reaction, but the reaction mechanism is not established. We herein report a comprehensive mechanistic study by in situ diffuse reflectance infrared Fourier transformed spectroscopy. Various types of surface species were observed to form upon C2 H2 and C2 H4 adsorption on CeO2 at different temperatures, including molecularly-adsorbed π-bonded and di-σ-bonded species, dissociatively-adsorbed species of C2 H and C2 H3, carbonates and formate species, and oligomers species, respectively. During the C2 H2 semihydrogenation reaction, the CeO2 surface is partially reduced and strongly hydroxylated. Both O and Ce sites on CeO2 are capable of catalyzing C2 H2 semihydrogenation reaction to C2 H4, and the O site is more active than the Ce site. The reaction mechanism was elucidated with observed molecularly-adsorbed C2 H2 species, a C2 H3 intermediate and adsorbed C2 H4 species on CeO2 . The π-bonded C2 H2 species at the O site was identified as the dominant active surface species for CeO2 -catalyzed C2 H2 semihydrogenation reaction. These results greatly advance the fundamental understanding of CeO2 -catalyzed C2 H2 semihydrogenation reaction.